2018
DOI: 10.1152/jn.00449.2017
|View full text |Cite
|
Sign up to set email alerts
|

Control of redundant pointing movements involving the wrist and forearm

Abstract: The musculoskeletal system can move in more ways than are strictly necessary, allowing many tasks to be accomplished with a variety of limb configurations. Why some configurations are preferred has been a focus of motor control research, but most studies have focused on shoulder-elbow or whole arm movements. This study focuses on movements involving forearm pronation-supination (PS), wrist flexion-extension (FE), and wrist radial-ulnar deviation (RUD) and elucidates how these three degrees of freedom (DOF) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Previous studies that focused on the control of orientation investigated similar rotational movements, but most of them applied joint constraints [35][36][37][38][39][40][41]. In our orientation matching task, the participants were free to use all the degrees of freedom of their arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that focused on the control of orientation investigated similar rotational movements, but most of them applied joint constraints [35][36][37][38][39][40][41]. In our orientation matching task, the participants were free to use all the degrees of freedom of their arm.…”
Section: Discussionmentioning
confidence: 99%
“…These stereotypical patterns were later attributed to strategies that use wrist flexion-extension and wrist radial-ulnar deviations, but not forearm pronation-supination [41]. A few studies also attempted to investigate adaptation to perturbations during wrist pointing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that focused on the control of orientation investigated similar rotational movements, but most of them applied joint constraints [37][38][39][40][41][42][43]. In our orientation-matching task, the participants were free to use all the degrees of freedom of their arm.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found robust motor invariants in kinematically redundant moderate pointing movements that involve both the wrist and the forearm, such as the fact that the cursor's path follows Donders' law for dimensionality reduction [40][41][42]. These stereotypical patterns were later attributed to strategies that use wrist flexion-extension and wrist radial-ulnar deviations, but not forearm pronation-supination [43]. A few studies also attempted to investigate adaptation to perturbations during wrist pointing.…”
Section: Introductionmentioning
confidence: 99%